PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DANA DESA DI DESA HARAPAN BARU KECAMATAN MANDAU KABUPATEN BENGKALIS PROVINSI RIAU - ", Markus; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in Harapan Baru Village, Mandau District, Bengkalis Regency of Riau Province with the problem (1) How is the community's participation in village fund management in Harapan Baru Village? (2) What factors affect community participation in village fund management in Harapan Baru village? The purpose of this research is to find out how people's participation in the management of Harapan Baru Village and Knowing factors that affect community participation towards village fund management in Harapan Baru Village. This research is quantitative research, the subject in this study is the village community of new hope. The respondents in this study were taken using random sampling techniques. Researchers took samples using a slovin formula with a sample count of 93 respondents. To collect data researchers used documentation guidelines and questionnaires. The results showed that community participation in village fund management is still low. The factors affecting community participation are still low. Keywords: Village Fund Management, Community Participati